The Implementation of Silent Demonstration Technique to Teach Writing Procedural Text in SMA Negeri 2 Sampang (RETAIN, 2017)
The Implementation of Silent Demonstration Technique to Teach Writing Procedural Text in SMA Negeri 2 Sampang Sri Muliyati English Education, Language and Art Faculty, State University Surabaya Srimuliyati046@gmail.com Drs. Fahri, M.A English Education Department, Faculty of Language and Art, State University of Surabaya fahri@unesa.ac.id Abstrak Menulis merupakan salah satu kemampuan berbahasa Inggris yang harus dikuasai oleh para pelajar bahasa kedua karena menulis merupakan salah satu kunci keberhasilan akademik. Namun,Siswa cenderung mengalami kesulitan dalam menulis teks prosedur karena mereka hanya menggunakan imajinasinya untuk menulis. Salah satu teknik terbaik yang dapat digunakan guru adalah teknik Silent Demonstration.Maka dari itu, penelitian ini bertujuan untuk mengetahui lebih dalam tentang implementasi teknik Silent Demonstration terhadap pembelajaran menulis teks prosedur, hasil tulisan siswa, serta respon mereka terhadap pengaplikasian teknik ini. Penelitian ini dirancang berdasarkan basic qualitative research. Subyek dari penelitian ini adalah seorang guru Bahasa Inggris dan siswanya kelas XII IPA 4 SMA Negeri 2 Sampang yang terdiri dari 26 siswa. Dalam penelitian ini, teknik pengumpulan data yang digunakan adalah observasi. Ada tiga instrumen yang digunakan dalam penelitian ini, yaitu field notes, tulisan siswa, dan wawancara. Berdasarkan hasil observasi, teknik Silent Demonstration adalah satu teknik yang bagus yang dapat digunakan untuk pembelajaran menulis teks prosedur. Guru di SMA Negeri 2 Sampang sukses dalam mengimplementasikan teknik ini dalam pembelajaran menulis di kelas. Kemudian, hasil dari tulisan siswa di pertemuan kedua menunjukkan hasil yang bagus dan memuaskan teruma dalam isi. Disamping itu, hasil dari wawancara siswa menunjukkan bahwa siswa memberi respon positif terhadap pengaplikasian teknik Silent Demonstration untuk pembelajaran menulis teks prosedur. Kesimpulannya, Silent Demonstration adalah salah satu teknik pembelajran terbaik yang dapat digunakan untuk pembelajaran teks prosedur. Pengimplementasian teknik ini dapat menstimulasi ide-ide siswa. Kata Kunci : Menulis, Prosedur Teks, Teknik Silent Demonstration Abstract Writing is one of the language skills that must be mastered by any foreign language learners because it is the key of academic success.However, students tend to get difficulties in writing procedure text because they only use their imagination to write.One of the best techniques which can be applied by the teacher to teach writing procedure text is Silent Demonstration technique.Therefore, this research was aimedto know deeply about the implementation of Silent Demonstration technique to teach writing procedural text, students compositionsand their responses toward this technique. This study was designed based on basic qualitative research.The subjects of this study were an English teacher and her students in XII-IPA 4of SMA Negeri 2 Sampang which consisted of 26 students. In this research, the data was collected through observation.There were three instruments used in this observation such as, field notes, students’ writing task, and interview. Based on the observation result, Silent Demonstration Technique is one of appropriate techniques that can be applied to teach writing procedural text. The teacher was successful in implementing this technique in writing class. Then, the results of the student’s composition in the second meeting were good, especially in term of content.Besides that, results of the students’ interview showed that the students gave positive responses toward the implementation of Silent Demonstration Technique to teach writing procedural text. In conclusion, Silent Demonstration Technique is one of the best techniques which can be applied in teaching writing procedural text. The implementation of Silent Demonstration technique can stimulate the students’ idea. . Keyword: Writing, procedure text, Silent Demonstration technique